A Randomized Controlled Exploratory Pilot Study to Evaluate the Effect of Rotigotine Transdermal Patch on Parkinson's Disease–Associated Chronic Pain. (31st December 2015) - Rascol, Olivier; Zesiewicz, Theresa; Chaudhuri, K. Ray; Asgharnejad, Mahnaz; Surmann, Erwin; Dohin, Elisabeth; Nilius, Sigrid; Bauer, Lars
Abstract: Pain is a troublesome nonmotor symptom of Parkinson's disease (PD). This double‐blind exploratory pilot study (NCT01744496) was the first to specifically investigate the effect of a dopamine agonist on PD‐associated pain as primary outcome. Patients with advanced PD (ie, receiving levodopa) and at least moderate PD‐associated chronic pain (≥3 months, ≥4 points on 11‐point Likert pain scale) were randomized to rotigotine (optimal/maximum dose ≤16 mg/24h) or placebo and maintained for 12 weeks. Primary efficacy variable was change in pain severity (Likert pain scale) from baseline to end of maintenance. Secondary variables included percentage of responders (≥2‐point Likert pain scale reduction), King's PD Pain Scale (KPPS) domains, and PD Questionnaire (PDQ‐8). Statistical analyses were exploratory. Of 68 randomized patients, 60 (rotigotine, 30; placebo, 30) were evaluable for efficacy. A numerical improvement in pain was observed in favor of rotigotine (Likert pain scale: least‐squares mean [95%CI] treatment difference, −0.76 [−1.87 to 0.34]; P = .172), and proportion of responders was 18/30 (60%) rotigotine vs 14/30 (47%) placebo. An ∼2‐fold numerical improvement in KPPS domain "fluctuation‐related pain" was observed with rotigotine vs placebo. Rotigotine improved PDQ‐8 vs placebo (−8.01 [−15.56 to −0.46]; P = .038). These results suggest rotigotine may improve PD‐associated pain; a large‐scale confirmatory study is needed.